DEVELOPING SCRAMBLE GAME USING CLASSDOJO AS STUDENTS’ MEDIA IN READING DESCRIPTIVE TEXT FOR THE SEVENTH GRADE STUDENTS OF SMP DHARMA PANCASILA MEDAN - Nurul Putri Jamalin; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This study deals with media in learning English especially reading descriptive text for the seventh-grade students. The objective of the study were to develop a Scramble Game using ClassDojo as a media in learning English especially descriptive text for junior high school. This study was conducted by research and development (R & D) design through six phases; gathering information and data, analyzing data, designing Scramble Game Using ClassDojo as media in descriptive text, validating by experts, revising, and final product. The subject of this research was the seventh-grade students of SMP Dharma Pancasila Medan. The instruments for collecting data were questionnaire and interview. The data were gathered by administering interview to the English teacher and distributing questionnaire to the seventh-grade students to get the students’ needs. The evaluators of the developed media were two experts namely an English lecturer and English teacher. The findings show that Scramble Game Using ClassDojo was able to be developed into media in learning English using the research method and needs analysis. The result of the research was the Scramble Game media that the teacher can use as the learning media of descriptive text for the seventh-grade students of junior high school. The developed media have been validated by experts. The total of validation score from the Expert I and Expert II are 91.8% so it was categorized “Very Good”. It means the developing Scramble Game Using ClassDojo are appropriate as media in reading descriptive text and can be used for the seventhgrade students of SMP Dharma Pancasila Medan in learning English especially descriptive text.Key Words: Research and Development (R&D), Reading, Media, Descriptive Text, Scramble Game, ClassDojo.